Cognitive selection mechanism for indoor propagation - Hashim, Wahidah; Ismail, Ahmad Fadzil; Dzulkifli, Sumayyah; Abd Ghafar, Nadratul Aliah (International Association of Computer Science and Information Technology Press, 2013)
The evolution of communication device demands for faster connection and higher data rates. This results in proliferation of new broadband technologies that are being introduced into the market for each interval of every 2 to 3 years. However, these technologies are still facing the challenge of unsatisfied users who request not only faster connection but also reliable connectivity. This paper proposes two cognitive selection mechanisms termed as successive and comparative selection which are applied in multiple broadband user terminals in order to maintain good connection rate. By employing such mechanisms, we can observe their performances in terms of optimized speed and switching delay. Cognitive radio aspects are also introduced within the selection system. These include sensing network condition capability, performing analysis and decision making for selecting the most optimum broadband network. The empirical study was conducted within the indoor environment of a residential area. The location was selected to vary the evaluation of the performance of these selection mechanisms. It was found that successive selection had shown a better optimized speed performance up to 37% improvement as compared to comparative selection. However, comparative selection shows a low switch delay performance in contrast to successive selection.